Perspectives on Chinese business and law / edited by Lukasz Golota [and three others]. - Gołota, Łukasz (Intersentia, 2018)
This book offers different perspectives on China's business and law. It aims to offer an introduction into both theoretical and practical aspects of China's law on foreign related business affairs. This comprises economic and political background information, including China's economic evolution and China-EU trade relations, in addition to more detailed information on selected subject areas important to foreign related business affairs in China, namely commercial arbitration law, contract law ,company law , IPR protection, financial law, foreign direct investment law, and also the establishment of overseas branches of Chinese companies in the EU. Perspectives on Chinese Business and Law thus introduces the reader to the current Chinese legislations on foreign related business. Dr Łukasz Gołota is Assistant Professor at the Institute of International Relations, Warsaw University, Section of Political Economy, Poland. Dr Jiaxiang Hu is Professor of Law at KuGuan Law School, Shanghai Jiao Tong University, China. Dr Kim Van Der Borght is Professor of International Economic Law & Diplomacy at the Vrije Universiteit Brussel, Belgium. Saisai Wang is a Lecturer of Law at the Law School of the Shandong University of Finance and Economics, China and a lawyer at Shandong Jointide Law Firm, China.